Imprinting and Early Exposure to Developed International Markets: The Case of the New Multinationals. Issue 3 (July 2018) - García-Canal, Esteban; Guillén, Mauro F.; Fernández, Paloma; Puig, Nuria
Previous research has analyzed the imprinting effect associated with the firm's international expansion without considering the full range of differences between home and host countries. These differences are important because, depending on the development gap, and the direction of the difference, learning opportunities and the possibility of upgrading firm's capabilities will be vastly different. For this reason, we analyze the specific influence of the exposure to a specific group of international markets, those that are more developed than the country of origin of the focal firm. Obviously, this exposure benefits especially firms from emerging and middle-income countries, which we refer to as "new multinationals." We analyze the different factors that influence the nature and intensity of the imprinting effect associated to the exposure to developed international markets by new multinationals.